Diabetes Mellitus Due to Liver Cirrhosis in 33-Year-Old Female - Henny Tanadi Tan; Suzanna Ndraha; Helena Fabiani; Fendra Wician; Mardi Santoso; Marshell Tendean (The Indonesian Society for Digestive Endoscopy, 2013)
Impaired glucose metabolism can occur in patient with chronic liver disease, either it is impaired glucose tolerance or diabetes mellitus (DM). DM due to liver cirrhosis is known as hepatogenous diabetes (HD). HDis different from type 2 DM in clinical signs and management.A 33-year-old female came with chief complaint of fatigue since three days before admission. Patient also complained of nausea, vomiting, and increased abdominal circumference since one year ago. Patient wasdiagnosed with DM two months ago. From physical examination, anemic and ascites without signs of cirrhosis were obtained. Laboratory test showed mild anemia with hemoglobin levels 6.5 g/dL, elevated serum bilirubinand liver enzymes, decreased serum albumin, prolonged prothrombin time and elevated random blood glucose. Serologic test showed chronic hepatitis B with HBV DNA 1.61 x 104 copy/mL. The abdominal ultrasound resultshowed liver cirrhosis with ascites.The patient was diagnosed with hepatogenous diabetes in liver cirrhosis due to chronic hepatitis B infection and anemia of chronic disease. The management of this patient was quite complex especially in administrationof oral antidiabetic agent which could affect the liver function.Keywords: hepatogenous diabetes, liver cirrhosis, diabetes mellitus, chronic hepatitis B infection